The clustering of disorders in infants born before the 28(th) week of gestation - Leviton, Alan (Acta Paediatr, 2010)
AIM: To see if disorders prevalent in infants born extremely preterm cluster. DESIGN: Observational cohort study SETTING: University-affiliated newborn intensive care nurseries SUBJECTS: 1223 infants born before the 28(th) week of gestation who survived until 36 weeks when the diagnosis of bronchopulmonary dysplasia (BPD) could be made. INTERVENTIONS: None MAIN OUTCOME MEASURES: An echolucent lesion of the cerebral white matter, moderate or severe ventriculomegaly on a protocol cranial ultrasound scan, BPD, retinopathy of prematurity (ROP), necrotizing enterocolitis (NEC), and early and late bacteremia. RESULTS: After adjustment for gestational age, children who had severe NEC (Bell stage IIIb) were at increased risk of severe ROP (stage 3+), severe BPD (defined as both oxygen and ventilator dependent), and late bacteremia. Children who had early bacteremia were at increased risk of late bacteremia and severe ROP. Those who had late bacteremia were at increased risk of severe ROP, while children who had severe ROP were at increased risk of severe BPD. CONCLUSIONS: NEC is the disorder common to most of the clusters, but we do not know if its onset occurred before the others. Organ-damage-promoting substances, however, have been found in the circulation of newborn animals with bowel inflammation, supporting the view that NEC contributes to the damage of other organs.